Short‐term impacts of cover crops in maritime potato (Solanum tuberosum) systems. Issue 2 (11th May 2022) - Una, Toby M.; McMoran, Don; Seefeldt, Steven S.; Maupin, Brian; Myhre, Elizabeth; Griffin‐LaHue, Deirdre
Abstract: Cover cropping is a soil conservation practice widely investigated in agronomic crops, but less is known about cover crop implications in specialty cropping systems, particularly in a high disturbance system like potato ( Solanum tuberosum L.). Brassica cover crops are popular in eastern Washington potato production, but brassica seed crop production in western Washington presents issues with use of brassica cover crops in the region's fresh‐market potato systems. To identify winter cover crops compatible with regional restrictions and climatic challenges in western Washington potato systems, trials including a no‐cover control, eight single species (including brassicas, grasses, and legumes), and a grass–legume mixture were conducted in Mount Vernon, WA, in 2018–2019 and 2019–2020. We examined cover crop and weed biomass production, potato yield and quality, and short‐term soil health impacts by measuring permanganate oxidizable carbon (POXC) and inorganic nitrogen before cover crop incorporation and at midseason. Cover crop biomass and weed suppression varied by year, with annual ryegrass ( Lolium multiflorum Lam .) producing the most biomass in both years despite poorer weather conditions and reduced cover crop biomass in other treatments in 2020, making it a good cover crop candidate for western Washington. Both POXC and inorganic nitrogen were greater at midseason but did not vary among cover crop treatments, suggesting that temporal variation influences POXC and inorganic nitrogen more than a single winter of cover crops. Potato yield and tuber wireworm damage varied by year, but not across cover crop treatments, and tuber symptoms resembling black scurf did not vary by year nor treatment. Core Ideas: Cover crops that produced higher biomass more effectively suppressed weeds in both years. Soil permanganate oxidizable C was influenced by sampling date but not by cover crops. Soil inorganic N at midseason was not affected by cover cropping. Cover crops did not affect potato tuber yield nor tuber quality.